(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, a road is constructed to solve the problem of delivering goods from the factory to a group of consumers by a single-road transport vehicle at the lowest cost. In this case, the cost of transportation is a function of vehicle loading and road quality. A matching mathematical model is built, in the case of a linear dependence of the travel cost by the amount of material transported, a linear integer model is obtained. In order to deliver goods at the lowest cost and according to the existing data, an algorithm was proposed to solve this problem and all arithmetic experiments were performed.